Compost quality optimization through Plackett-Burman’s design - Ortiz Dongo, Luis Felipe (2024)
Purpose: This research aimed at compost quality optimization through Plackett-Burman’s design application.This statistical method was used to identify and evaluate key factors that impact compost quality and determine its optimal levels. Method: Eight experiments were carried out with variables such as leachate recirculation, Carbon/Nitrogen ratio,manure type, bacterial and fungi incorporation, type of plant material, and compost pile height. Results: Obtained results revealed significant influence of guinea pig manure in compost quality, improving pH and electric conductivity (dS∙m-1) values, as well as its influence on purple corn fresh and dry weight increase. However, the use of guinea pig manure can increase arsenic, mercury, and lead compost levels, but within the range allowed by Peruvian technical standards. Leachate recirculation showed significant effect on compost humidity increase, which decreased its physical quality to not permitted values by Peruvian technical standards. In addition, leachate uses a reduced number of corn leaves, as well as its fresh and dry weight. It was possible to identify optimal conditions to maximize composting process efficiency, through Plackett-Burman’s Design. Conclusion: These findings provide a solid foundation for composting practice's continuous improvement, contributing to high-quality organic fertilizer production more efficiently and sustainably. This study has the potential to guide future research and feasible applications in the agricultural field, favoring more environmentally friendly practices adoption.